Medical Data Leakage in Healthcare: A Systematic Literature Review of Cybersecurity, Legal Issues, and Patient Privacy - Ade Netra Kartika; Ahmad Redi (Indonesian Journal Publisher, 2026)
Medical data leakage has become one of the most critical challenges facing healthcare organizations as digital health technologies, electronic health records (EHRs), artificial intelligence, cloud computing, and interconnected medical devices continue to expand. Beyond compromising sensitive patient information, data leakage threatens patient safety, institutional trust, and regulatory compliance. This study systematically reviews the existing literature to examine the causes, consequences, legal implications, and prevention strategies of medical data leakage in healthcare. A Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted. The literature was identified from Scopus, PubMed, and Web of Science, complemented by backward and forward snowballing. Fourteen peer-reviewed studies that met the preliminary eligibility criteria were included in the thematic synthesis. The retrieved studies were analyzed using evidence mapping, thematic coding, and narrative synthesis. Three major themes emerged from the analysis: (1) healthcare cybersecurity vulnerabilities, (2) medical data leakage and patient privacy, and (3) legal protection and healthcare governance. The findings indicate that medical data leakage is not solely a technical cybersecurity issue but results from the interaction of technological vulnerabilities, human behavior, organizational governance, and regulatory implementation. The review proposes an integrated thematic synthesis framework linking cybersecurity vulnerabilities, medical data leakage pathways, legal protection, and governance responses to strengthen healthcare cyber resilience. The findings provide practical implications for healthcare organizations, policymakers, and researchers in developing comprehensive strategies for protecting medical information in an increasingly digital healthcare environment.